A STRATEGY DEVELOPMENT FOR A SMOOTH TRANSITION INTO THE REMOTE STUDIES IN LATVIAN EDUCATION INSTITUTIONS IN A PANDEMIC - Jevgenija Dehtjare; Igors Babics; Olga Verdenhofa; Viktoriia Riashchenko (Izdevnieciba "Baltija Publishing", 2020)
The aim of the abstract is to investigate challenges the secondary and higher education institutions face during the pandemic times in Latvia and to discuss strategy to be developed in an order to ensure smooth transition into the remote study process with the help of a technological inventory appropriate to be used for remote study process. Challenges both secondary and higher education institutions and their staff experience have to be analysed as well, altogether with the outcomes. A combination of the remote and in-class education, issues and benefits are overviewed in the paper as well. ISMA, the University of Applied Sciences and its transition approach were examined thus establishing strong practical benefit of the research. The research problem is to analyse existing challenges education establishments in Latvia used to face with during the period of pandemic and to examine solution strategy and tools to be applied in an order to establish smooth transition from in-class to a remote study process. The conclusion of the research: no doubts the establishment of the transition process from in present studies into the remote mode was challenging and complicated, however it was realised in a consonance of the frameworks and recommendations designed both by the European and Latvian public bodies. The process of remote studies is challenging, still many advantages were discovered and this let to conclude the approach of combined education has a right to be applied even after the pandemic is over. The outcomes of the research are also beneficial for other educational establishments of Latvia and abroad, thus ensuring known approach when rapid and clear transition strategies must be taken. The developed strategy might be applied in case if there is a necessity to ensure establishment of remote studies within short period of time.